Comparative effects of methamphetamine, cannabis, and polysubstance use on oral health - Kılıç, Osman Hasan Tahsin; Kürklü Arpaçay, Duygu; Gezen, Onur Çağdaş; Bayram, Zehra Nur; Başer, Aysel (Frontiers in Psychiatry, 2025)
IntroductionThis study aimed to compare the clinical oral health status of individuals with Methamphetamine (MA), Cannabis (THC), and Polysubstance (PS) use disorders to healthy controls, and assess the impact of substance type, usage duration, quantity, and oral health behaviors on dental health outcomes through comprehensive oral examinations.MethodsThis cross-sectional clinical study was conducted at İzmir Democracy University Buca Seyfi Demirsoy Education and Research Hospital between April 2024 and August 2024. A total of 190 individuals with substance use disorders (MA, THC, and PS users) and 91 healthy controls participated. Sociodemographic data, substance use history, and oral health behaviors were collected using a researcher-developed questionnaire and the Turkish version of the Hiroshima University Dental Behavior Inventory (HU-DBI). Oral health status was assessed through clinical oral examinations using the Decayed, Missing, and Filled Teeth (DMFT) index. Statistical analyses were performed using SPSS 26.0, applying t-tests, ANOVA, Chi-square tests, and Pearson correlation to evaluate group differences and relationships between variables. A p-value of < 0.05 was considered statistically significant.ResultsThe study revealed significant differences in oral health among substance users compared to the control group. MA users had the highest DMFT scores (11.04 ± 5.56), followed by THC users (9.49 ± 5.87), and PS users (8.40 ± 4.52), with the control group showing the lowest scores (6.08 ± 4.18) (p<0.001). The study also found a moderate positive correlation between MA use and DMFT scores, indicating that longer and higher usage leads to poorer oral health, while no significant association was observed between THC use and DMFT scores. Additionally, significant disparities in education levels were observed, with substance users having lower education compared to controls (p=0.001). HU-DBI scores indicated poorer oral health behaviors in substance users, though the difference was not statistically significant (p=0.053).DiscussionThe study reveals that all substance use groups, including MA, THC, and PS users, exhibit significantly poorer oral health outcomes, with higher DMFT scores and worse oral health behaviors compared to the control group, highlighting the critical need for comprehensive dental care interventions for individuals with substance use disorders.Clinical Trial Registrationhttps://clinicaltrials.gov/study/NCT06640712, identifier NCT06640712.